2020
DOI: 10.1002/jdd.12428
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with dental treatment at a university dental clinic: A qualitative analysis

Abstract: Purpose/Objectives The aim for this study was to identify important factors influencing patient satisfaction in a university dental clinic, through qualitative analysis. Methods From June 1, 2014 to January 30, 2018, 7827 patient satisfaction surveys were collected. A thematic analysis was conducted on the 10,956 patient responses to 3 open‐ended questions. A thematic coding dictionary was inductively developed using thematic analysis managed with MAXQDA 2018 Standard, a qualitative data management software pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The results of this study indicated that socioeconomic and individual factors and the source of information used to obtain dental information were associated with a lower level of OHL. An accurate understanding of the patients' levels of OHL and their determinants can contribute to dental students and professionals to adapt the communication processes and clinical environment to improve the quality of care and oral health outcomes 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that socioeconomic and individual factors and the source of information used to obtain dental information were associated with a lower level of OHL. An accurate understanding of the patients' levels of OHL and their determinants can contribute to dental students and professionals to adapt the communication processes and clinical environment to improve the quality of care and oral health outcomes 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…The educational progress and person-centered care are reinforced by sharing knowledge between the academic institutions and corporations. 1,2 Such key collaborations may facilitate exposure to continuing education (CE) programs, foster life-long learning, and further support the increased interest of recent graduates in CE.…”
Section: Problemmentioning
confidence: 99%
“…To facilitate a meaningful learning environment, best practices recommend highlighting the similarities and differences between the novel material substitutes and the traditional solutions using the autogenous graft, the “gold standard”. The educational progress and person‐centered care are reinforced by sharing knowledge between the academic institutions and corporations 1,2 . Such key collaborations may facilitate exposure to continuing education (CE) programs, foster life‐long learning, and further support the increased interest of recent graduates in CE.…”
Section: Problemmentioning
confidence: 99%
“…10 Additionally, demographic factors such as the age of the patient and the gender of the clinician may also affect patients' satisfaction. [11][12][13] Besides that, patient familiarity with the clinicians and their experience receiving treatment affects the satisfaction in communicating with their clinician. 14 Thus, the realization of the importance of communication skills in dentistry has led to dental schools now providing their students with skills-based communication components in their curriculum.…”
Section: Introductionmentioning
confidence: 99%